Thermal Performance Analysis of Functional Parameters of the Floor Heating System in Africa - Safaa Oubenmoh; Charraou, Afaf; Saadani, Rachid; Rahmoune, Miloud; Ait msaad, Abdelouahad; Jamil, Abdelmajid; Sebbar, El hassan (Statistics, Optimization & Information Computing, 2023)
Buildings frequently utilize radiant heating floors because they offer benefits including effective use of space and homogeneous temperature distribution, which results in increased thermal comfort. The present work aims to investigate the perfect use of floor heating systems analytically and numerically with improved thermal performance to prove their efffficiency in various African climates. The evaluation depends on the functional parameters of the heating system and particularly focuses on floor surface temperature to acquire the desired heat flux and the perfect supply water temperature. According to results, It is desirable to use floor coverings with low thermal resistance and should not exceed R = 0.15 m2 . K/W since it has considerable influence on the thermal efffficiency of the underfloor heating components. The pipe diameter is suggested to be about 20 mm. By comparing pipe spacings of 15 mm and 30 mm, the difference in supply water temperature is approximately 7.4 C. The smaller the pipe spacing, the more energy it delivers and makes the floor much warmer while reducing heating time. Regarding the effect of pipe materials, PE-X is chosen for this study because of its low cost and resistance to corrosion and scaling. As the influence of these studied parameters on floor heating is remarkable, there is also the impact of the ambient temperature of each city on the floor heating efffficiency. The proposed model can be applied and considered potentially beneficial and helpful to the control, and design of floor heating systems, and choosing the right heating source.